How Human Relations Drive Employee Performance: The Mediating Role of Employee Well-being in Indonesia's Consumer Finance Industry - Dian Indriani; Mattalatta Mattalatta; Gunawan Gunawan; Hasmin Hasmin; Kurniawaty Kurniawaty; Ansar Ansar (Yayasan Vifada Cendikia Indonesia, 2026)
Purpose: This study examines the effect of human relations on employee performance and investigates the mediating role of employee well-being in Indonesia's consumer finance industry. Research Method: A quantitative explanatory research design was employed using survey data collected from 220 permanent employees of consumer finance companies in Makassar, Indonesia, selected through purposive sampling. The proposed hypotheses were tested using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Results and Discussion: The findings reveal that human relations positively and significantly influence both employee well-being and employee performance. Employee well-being also exerts a positive effect on employee performance and partially mediates the relationship between human relations and employee performance. These results suggest that effective interpersonal relationships characterized by communication, trust, teamwork, and social support enhance employee well-being, which subsequently improves individual performance. Implications: The findings provide practical guidance for managers in consumer finance companies to strengthen interpersonal relationships and employee well-being as strategic human resource initiatives to improve organizational performance. Future studies are encouraged to examine additional organizational and psychological factors across broader industrial settings. Originality: This study extends the integration of Social Exchange Theory, Job Demands–Resources Theory, and Conservation of Resources Theory by demonstrating the mediating role of employee well-being in explaining how human relations enhance employee performance within Indonesia's consumer finance industry.